Acute Myeloid Leukemia Minimal Residual Disease Detection: The Difference from Normal Approach. Issue 1 (20th April 2020) - Wood, Brent L.
Abstract: The identification of residual leukemia following therapy, termed minimal or measurable residual disease (MRD), has emerged as one of the most important prognostic factors for patients with acute leukemia, including acute myeloid leukemia (AML). Flow cytometry is a preferred method for MRD detection due to its general applicability and the rapid results that it makes available. In this article, the basic protocol outlines a simple and efficient method for the labeling of hematopoietic cells from bone marrow or peripheral blood with a panel of monoclonal antibodies designed both to highlight patterns of normal maturation and allow identification of neoplastic hematopoietic progenitor populations with a high degree of sensitivity and specificity. The method was developed in a clinical laboratory setting for the diagnosis of myeloid stem cell disorders and neoplasms, and has been extensively validated both technically and clinically for the detection of MRD in AML. © 2020 The Authors. Basic Protocol : Staining and flow cytometry for AML minimal residual disease detection Support Protocol : Analysis and interpretation of data for AML minimal residual disease detection